2019
DOI: 10.1016/j.resuscitation.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Variation in outcomes among 24/7 percutaneous coronary intervention centres for patients resuscitated from out-of-hospital cardiac arrest

Abstract: Background: Patients treated at 24/7 percutaneous coronary intervention (PCI) centres following out-of-hospital cardiac arrest (OHCA) have better outcomes than those treated at non-24/7 PCI centres. However, variation in outcomes between 24/7 PCI centres is not well studied. Objectives: To evaluate variation in outcomes among 24/7 PCI centres and to assess stability of 24/7 PCI centre performance. Methods: Adult patients in the California Office of Statewide Health Planning and Development Patient Discharge Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(51 reference statements)
1
1
0
Order By: Relevance
“…Mumma et al reported significant variation in good neurological recovery following OHCA between 128 hospitals where PCI is available 24 hours/7 days in California, USA. Multivariable hierarchical logistic regression models were constructed (adjusted rates of good neurological recovery, 18% to 39%; p<0.001) 28. Our present study corroborated this prior study and confirmed the between-hospital variation in survival and functional outcome after OHCA in different healthcare settings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Mumma et al reported significant variation in good neurological recovery following OHCA between 128 hospitals where PCI is available 24 hours/7 days in California, USA. Multivariable hierarchical logistic regression models were constructed (adjusted rates of good neurological recovery, 18% to 39%; p<0.001) 28. Our present study corroborated this prior study and confirmed the between-hospital variation in survival and functional outcome after OHCA in different healthcare settings.…”
Section: Discussionsupporting
confidence: 88%
“…The between-hospital variation might result from the hospital characteristics that prior studies reported, such as OHCA case volume,17–19 29 30 and cath-lab availability (24/7 PCI or limited PCI capability) 30–32. However, in Mumma’s study, the between-hospital variation in good neurological recovery following OHCA existed even though hospitals with similar characteristics (24/7 PCI centre) were incorporated 28. These results suggest that there were unmeasured hospital characteristics causing the between-hospital variation.…”
Section: Discussionmentioning
confidence: 92%